Growth traits of the Dorper sheep. I. Factors influencing growth traits - Inyangala, B.A.O.; Rege, J.E.O.; Itulya, S. (International Livestock Centre for Africa, 1992)
Presents results of a study carried out to analyse growth traits of the Dorper sheep. Data on 969 lambs collected over a 10-year period (1978 to 1987) at Magogo, Kenya were used in the study. Lamb traits studied were weights from birth to yearling and absolute growth rates between adjacent stages of growth. All the fixed effects studied influenced growth in one way or another.